ЩОДО ПРАВОМІРНОСТІ ЗДІЙСНЕННЯ ФУНКЦІЙ ОХОРОНИ ГРОМАДСЬКОГО ПОРЯДКУ НЕДЕРЖАВНИМИ МІЛІТАРИЗОВАНИМИ ФОРМУВАННЯМИ - Комзюк, Альона Валентинівна (SUPREMANCE OF LAW, 2018)
The legal bases for citizens’ participation in the protection of public order through the example of determining the lawfulness of the exercising of public order protection functions by non-state militarized formations are analyzed in the article. It is noted that in recent years, the activity of public formations increased in Ukraine, in relation to which there is no existing information on the legal grounds for their organization and functioning. It was concluded concerning the inadmissibility of the creation and operation of any public, especially militarized, formations with violation of the procedure established by law.